Isomon instabilities driven by energetic ions in Wendelstein 7-X. (4th May 2016) - Kolesnichenko, Ya.I.; Könies, A.; Lutsenko, V.V.; Drevlak, M.; Turkin, Yu.; Helander, P.
Abstract: It is found that modes of Alfvénic character affected by plasma compressibility and having equal poloidal and toroidal mode numbers (named 'isomon modes') can exist in W7-X. These modes, and the conditions under which they arise, are sensitive to the magnitude of the rotational transform of the field lines and the presence of energetic ions. The energetic ions produced by neutral-beam injection (having the energy 55–60 keV) interact resonantly with large-scale isomon modes ( m = n ≪ 10 ), which tends to lead to instabilities extending over a large part of the plasma cross section.